The BELARE 2019-2020 meteorite recovery expedition on the Nansen Ice Field, East Antarctica - Shirai, Naoki; Goderis, Steven; Yesiltas, Mehmet; Pourkhorsandi, Hamed; Poudelet, Manu; Leitl, Martin; Yamaguchi, Akira; Debaille, Vinciane; Claeys, Philippe (2020)
The 11th Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites, Thu. 3 Dec. conference object